Influence of DNA–dye complex stability on separation resolution in microchip electrophoresis. (March 2012) - Lo, Roger C; Joffe, Aaron M
Background: Different markers have been used to label DNA for sample detection in gel electrophoresis. Intercalating dyes, (e.g., YOYO) have been widely used to label DNA for sample detection, because they do not require the use of radioisotopes, covalent attachment or enzyme reactions. The labeling of DNA fragments can be achieved by simply mixing solutions of the intercalating dye and DNA sample. However, the separation quality of DNA labeled with intercalating dyes is greatly influenced by the buffer used, which affects the DNA–dye complex stability.Results: In this study, we investigated the effects of DNA–dye complex stability on separation resolution of dsDNA migrating in a photopolymerized polyacrylamide gel by measuring mobility and dispersion coefficients on a microfluidic chip and comparing predicted separation resolution under different dye and buffer conditions.Conclusion: We found that a buffer containing tetrapentylammonium (NPe4 + ) yielded better separation resolution than the frequently used TBE buffer on our microchip electrophoresis system.